Delineation of subsurface features by electrical resistivity tomography and induced polarization in upstream basin of Chaq-Chaq dam – northeastern Iraq - AMIN, Abdulla K.; MOHAMMED, Sazan S.; BABAN, Ezzadin N. (Contributions to Geophysics and Geodesy, 2024)
The construction of dam is important for many reasons. Prior to construction, it is essential to assess the dam's base reservoir to identify any subsurface cavities. This study was conducted along nine electrical resistivity (ERT) profiles and eight induced polarization (IP) profiles, which are traditional ERT profiles, trending SW to NE direction in the reservoir part of the failed Chaq-Chaq dam NW of Sulaimaniyah city. The aim of this study was to delineate subsurface layers, underground features, determine the depth to bedrock, and investigate indications of the causes of collapse of the constructed Chaq-Chaq dam. The Res2Dinvx64 program used in the inversion method to obtain true 2D resistivity sections using a Schlumberger-Wenner array, which is highly sensitive to changes in resistivity both vertically and laterally. Based on the resistivity values, it was found that the area consists of three geological layers; the first layer consists of soil, while the second layer consists of rock fragments, the interface between them has disappeared because the first layer is thin, and the third layer is specified as consolidated and cohesive limestone of the Kometan Formation. The surface of the Kometan limestones is irregular due to weathering and faulting resulting from tectonic movements leading to the collapse of the area and later filled with sediments of recent deposition. The IP method was only used to distinguish clay and water. According to IP values, water is present in the subsurface of the study area. According to the ERT sections, a sinkhole with a depth range of (15 – 39 m) was encountered at the beginning of most of the profiles.